Exploring the Implementation and Implications of AI-Based Media in Chemistry Learning at Secondary Level: A Systematic Literature Review - Fa'ari Salsabiila; Anti Kolonial Prodjosantoso (Universitas Sebelas Maret, 2026)
This study aims to systematically examine the implementation and implications of Artificial Intelligence (AI)-based media in chemistry learning at the secondary education level. Using the Systematic Literature Review (SLR) approach which refers to the PRISMA guidelines, as many as 19 scientific articles from the Science Direct database were analyzed qualitatively. The research focus includes the identification of the types of AI media used, the chemical topics supported by AI, the form of implementation in the classroom, as well as the pedagogical implications of the integration of AI in learning. The results show that the most widely used AI media is generative chatbots such as ChatGPT, Gemini, and Claude, followed by immersive technologies such as Virtual Reality (VR) and Augmented Reality (AR). This media is used to improve students' understanding of concepts, especially in abstract topics such as atomic structure, molecular visualization, and organic reactions. However, a number of challenges were found, including inaccurate content, low digital literacy, ethical and academic integrity issues, and limited technological infrastructure. On the other hand, AI media also opens up opportunities for adaptive and personalized learning, increased student learning engagement, and teacher efficiency in learning planning. . This study recommends strengthening teacher training, ethical policies, and adaptive curriculum design to support the optimal application of AI in chemistry learning in the digital era.